Educational And Economical Relations Between Turkey and Uzbekistan During the First World War (Eurasian Research Bulletin, 2023)
In this article, the topic of mutual relations between Turkistan (is now Uzbekistan) and Turkey during the First World War is based on archival data, as well as sources based on historical works and memory books that provide information about this period political, cultural, educational and educational relations between the two countries are highlighted. Also, this article and educational spheres between the two countries, relations of mutual cooperation will be highlighted. Also, this article sheds light on the material and moral support of Turkistan to Turkey during the First World War. Turkish soldiers captured during the First World War, their participation in the social, economic, spiritual and cultural life of Turkistan, are studied and analyzed based on historical sources